U-shaped relationship between managerial herd behavior and corporate financialization with the moderating effect of corporate governance: evidence from China - Wang, Fangyun; Hu, Wenxiu; Liu, Li; Yang, Li (Journal of Business Economics and Management, 2023)
Based on behavioral finance theory, we discuss the influence of managers’ herd behavior on corporate financialization from the perspective of managers’ behavioral preferences. Empirical testing was conducted using data from nonfinancial listed firms on the Shanghai and Shenzhen A-shares from 2007 to 2021 and a U-shaped relationship was found between managerial herd behavior and corporate financialization. When managerial herd behavior is within an appropriate range, the increase in managerial herd behavior has a negative influence on corporate financialization. In contrast, excessive managerial herd behavior leads to excessive corporate financialization. Additionally, corporate governance has a weakening effect on this relationship. Heterogeneity analyses indicate significant disparities in the effect of managerial herd behavior on corporate financialization among enterprises with diverse ownership structures. Finally, corporate financialization and innovation investments have an inverted U-shaped relationship, and their relationship is moderated positively by management herd behavior. Our results have strong practical significance for fostering the balanced growth of the financial sector and the real economy. First published online 05 January 2024